2001
DOI: 10.2134/jeq2001.303934x
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Arsenic, Copper, Lead, Thallium, and Zinc to Various Vegetables Grown in Slag‐Contaminated Soils

Abstract: To anticipate a possible hazard resulting from the plant uptake of metals from slag-contaminated soils, it is useful to study whether vegetables exist that are able to mobilize a given metal in the slag to a larger proportion than in an uncontaminated control soil. For this purpose, we studied the soil to plant transfer of arsenic, copper, lead, thallium, and zinc by the vegetables bean (Phaseolus vulgaris L. 'dwarf bean Modus'), kohlrabi (Brassica oleracea var. gongylodes L.), mangold (Beta vulgaris var. macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 15 publications
(15 reference statements)
3
35
1
1
Order By: Relevance
“…Plants grown in mine-tailing amended soils take a smaller proportion of metals when compared to plants in control areas (19,20) with an effect that is most severe for the metals Cu and Pb and least severe for the metals Zn and Cd.…”
Section: Metal Mixtures and Kids: Exposure And Dosementioning
confidence: 99%
“…Plants grown in mine-tailing amended soils take a smaller proportion of metals when compared to plants in control areas (19,20) with an effect that is most severe for the metals Cu and Pb and least severe for the metals Zn and Cd.…”
Section: Metal Mixtures and Kids: Exposure And Dosementioning
confidence: 99%
“…According to this study, the bioavailable ratio of studied metals has the order: Pb> Cu> Zn, which is quite similar to that order of the present study for the collected stream sediment samples. It could be concluded that metals exhibit various bioavailability ratios in different soil types, and the bioavailability fractions depend on many factors, including metal species, plan types, and soil parameters such as cation exchange capacity, pH, and redox potential [26,27].…”
Section: Bioavailable Ratiomentioning
confidence: 99%
“…In recent past, Bunzl et al (2001) investigated soil to plant transfer of heavy metals like, Cu, Pb and Zn by vegetables. Studies on heavy metal uptake reveled that vegetables grown at environmentally contaminated sites in Addis Ababa, Tanzania, could take up and accumulate metals at levels that are toxic to human health.…”
Section: Introductionmentioning
confidence: 99%